2019
DOI: 10.1007/s42399-019-00208-9
|View full text |Cite
|
Sign up to set email alerts
|

First Autochthonous Case of Cryptococcal Meningitis in an Immunocompetent Host Due to Cryptococcus gattii VGIin Northern Italy

Abstract: We describe a case of cryptococcal meningitis diagnosed in an immunocompetent patient, with no apparent predisposing conditions, living in Northern Italy. The patient was initially admitted for visual disturbs with nausea and cervical pain, but magnetic resonance imaging of the brain showed a diencephalic lesion. Colonies of Cryptococcus gattii species complex were isolated from cerebrospinal fluid. Antifungal therapy was started and conditions of the patient improved in 2 months. The fungal isolate was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A further study identified where the potential risk of contact with the fungus is higher and revealed that more than 137 million people are potentially involved (Alaniz et al, 2020). In the last decades, cases of cryptococcosis due to C. gattii VGI in Europe have increased compared to the almost absence of cases reported in the past, with half of the cases occurred in immunocompetent hosts (Andreou et al, 2019;Hagen et al, 2012;Iatta et al, 2012;McCormick-Smith et al, 2015;Passera et al, 2020). Considering the above epidemiological picture, it is fundamental to carefully monitor both the occurrence of new clinical cases and the environmental distribution of the fungus to promptly detect the onset of possible outbreaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further study identified where the potential risk of contact with the fungus is higher and revealed that more than 137 million people are potentially involved (Alaniz et al, 2020). In the last decades, cases of cryptococcosis due to C. gattii VGI in Europe have increased compared to the almost absence of cases reported in the past, with half of the cases occurred in immunocompetent hosts (Andreou et al, 2019;Hagen et al, 2012;Iatta et al, 2012;McCormick-Smith et al, 2015;Passera et al, 2020). Considering the above epidemiological picture, it is fundamental to carefully monitor both the occurrence of new clinical cases and the environmental distribution of the fungus to promptly detect the onset of possible outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…neoformans and C . gattii species complex isolates which have been genotyped (Andreou et al ., 2019; Baró et al ., 1998; Chowdhary et al ., 2012; Cogliati, 2013; Cogliati et al ., 2016; Colom et al ., 2005; Colom et al ., 2012; Gerontiti et al ., 2017; Hagen et al ., 2012; Iatta et al ., 2012; Maestrale et al ., 2015; Mahmoud, 1999; Montagna et al ., 1997; Montagna et al ., 2018; Morera et al ., 2011; Mseddi et al ., 2011; Passera et al ., 2020; Romeo et al ., 2012; Solla et al ., 2008; Tortorano et al ., 1997; Trovato et al ., 2019; Velegraki et al ., 2001). Furthermore, genotyping and phylogenetic analysis of the European VGI isolates showed the presence of a genotypic cluster endemic in the continent confirming that bioclimatic conditions of Europe are suitable for the survival of this fungus (Hagen et al ., 2012; Cogliati et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%